Prevalence of stress, anxiety, depression and its associated factors among undergraduate medical students of Thrissur district during COVID-19 pandemic: a cross-sectional study - M. V., Sruthi; V., Chandana; Benoy, Bilhan; Anuda, Ayisha; Krishnan, Aswathi Krishnan (International Journal Of Community Medicine And Public Health, 2023)
Background: The COVID-19 pandemic and lockdown has aggravated mental health problems among the student community. But due to pandemic restrictions the medical students lack the clinical exposure and interaction with patients and were forced to learn through online platform, which affected their procurement of clinical and communication skills. This led to lot of stress among medical students, which needs to be evaluated and managed. Objectives were to study the prevalence of stress, anxiety, depression and its associated factors among undergraduate medical students of Thrissur district during COVID-19 pandemic. Methods: A cross- sectional study was undertaken among undergraduate medical students from July 2021 to Jan 2022. Total 205 undergraduate medical students from all batches were included in the study and data was collected with the help of Google forms and a self-administered DASS 21 questionnaire was used as a tool for assessing the prevalence of depression, anxiety and stress among medical students. Results: Out of 205 undergraduate medical students, 106 (51.7%) were suffering from anxiety, 70 (34.1%) were suffering from stress and 119 (58%) were suffering from depression. Around 112 (54.6%) of students faced difficulty in paying academic fees and 127 (62%) of students had difficulty due to cut shorting of clinical postings. The female students had higher prevalence of stress and anxiety compared with males which was statistically significant (p=0.04, 0.01 respectively). Conclusions: The presence of depression, anxiety and stress was prevalent among medical students. It has to be addressed with mentorship programmes, counselling and by ensuring leisure activities in the campus.